College Students’ Perceptions of Concurrent/Successive Nonverbal Behaviors as Sexual Consent - King, Bruce M. (Journal of interpersonal violence, 2021)
In previous studies, researchers had students rate single nonverbal behaviors as signals conveying and inferring sexual consent. In real-life interactions, young people use an array of behaviors occurring concurrently or successively to interpret sexual consent. With use of a 7-point scale (0 = Definitely No, 6 = Definitely Yes), students at a southeast public university were asked to rate their perceptions of nine nonverbal behaviors as signals of sexual consent, nine combinations of two of those behaviors, and eight combinations of three behaviors. There were significant effects for both gender and number of behaviors (p < .001). Over 43% of women answered “0” to all behaviors and combinations of behaviors, whereas only 20.3% of men answered “0” to all. The mean ratings for men were greater than those for women under all three conditions and increased with the number of behaviors. At least one third of men responded with “3” (the midpoint of the scale) or greater to seven of the eight combinations of three behaviors, whereas the percentage of women responding “3” or greater never exceeded 18% for any of the individual behaviors or combinations. It is concluded that as the number of nonverbal behaviors increases the subjective interpretation of sexual consent also increases, thus also increasing the chances of unwanted sexual advances.